Trees at the Amazonia-Cerrado transition are approaching high temperature thresholds. (1st March 2021) - Araújo, Igor; Marimon, Beatriz S; Scalon, Marina C; Fauset, Sophie; Marimon Junior, Ben Hur; Tiwari, Rakesh; Galbraith, David R; Gloor, Manuel U
Abstract: Land regions are warming rapidly. While in a warming world at extra-tropical latitudes vegetation adapted to higher temperatures may move in from lower latitudes this is not possible in the tropics. Thus, the limits of plant functioning will determine the nature and composition of future vegetation. The most temperature sensitive component of photosynthesis is photosystem II. Here we report the thermal safety margin (difference between photosystem II thermotolerance (T50 ) and maximum leaf temperature) during the beginning of the dry season for four tree species co-occurring across the forest-savanna transition zone in Brazil, a region which has warmed particularly rapidly over the recent decades. The species selected are evergreen in forests but deciduous in savannas. We find that thermotolerance declines with growth temperature >40 °C for individuals in the savannas. Current maximum leaf temperatures exceed T50 in some species and will exceed T50 in a 2.5 °C warmer world in most species evaluated. Despite plasticity in leaf thermal traits to increase leaf cooling in hotter environments, the results show this is not sufficient to maintain a safe thermal safety margin in hotter savannas. Overall, the results suggest that tropical forests may become increasingly deciduous and savanna-like in the future.